2015
DOI: 10.1210/en.2014-1943
|View full text |Cite|
|
Sign up to set email alerts
|

Thyrostimulin Regulates Osteoblastic Bone Formation During Early Skeletal Development

Abstract: The ancestral glycoprotein hormone thyrostimulin is a heterodimer of unique glycoprotein hormone subunit alpha (GPA)2 and glycoprotein hormone subunit beta (GPB)5 subunits with high affinity for the TSH receptor. Transgenic overexpression of GPB5 in mice results in cranial abnormalities, but the role of thyrostimulin in bone remains unknown. We hypothesized that thyrostimulin exerts paracrine actions in bone and determined: 1) GPA2 and GPB5 expression in osteoblasts and osteoclasts, 2) the skeletal consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…In the present study, the expression of gphb5 in the skin cells is in accordance to that found in humans [42]. Furthermore, it has been recently shown that gphb5 plays a paracrine role in skeletal development and bone formation [41]. In light of the above, our results may suggest that gphb5 is expressed in the skin of the lower jaw and induce changes in cartilage or bone cells located at short distance.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, the expression of gphb5 in the skin cells is in accordance to that found in humans [42]. Furthermore, it has been recently shown that gphb5 plays a paracrine role in skeletal development and bone formation [41]. In light of the above, our results may suggest that gphb5 is expressed in the skin of the lower jaw and induce changes in cartilage or bone cells located at short distance.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the primary role of the hormone is still unknown [41]. Gphb5 seems to have a paracrine rather than an endocrine function, implying that it can be expressed locally and induce changes in nearby cells [40, 41]. In the present study, the expression of gphb5 in the skin cells is in accordance to that found in humans [42].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Still, further research is needed into the mechanism of thyrostimulin in bone metabolism, as this is unclear. It does not induce a cAMP response in primary osteoblasts or osteoclasts, in addition to failing to activate noncanonical signaling pathways (Bassett et al 2015).…”
Section: Th E Functional Role Of Thyrostimulinmentioning
confidence: 99%